Human Resources Development of Sharia Banking: Phenomenological Approach - Yusuf, Burhanuddin (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2015)
The aims of this study are to finding, identifying and mapping the condition and situation of the policy and practice of Human Resource Management. This study used a qualitative method with phenomenological approach to uncover the professional development of HR qualify. Data analysis techniques includes reduction, data display, perform verification, and compiling data to draw the conclusions. The study concluded that the conditions of management and human resource development three sharia Bank in Jakarta refers to the philosophy and principles of Islamic economics as well as guided by the vision and mission of sharia banks. This study find that sharia HR professional qualification characterised by quality of faith, piety, knowledge and understanding of finance and business, applying the principles of Islam and has a strong commitment to apply the rules of sharia, noble, hard-working, and sincerely intelligent accompanied by sincereDOI: 10.15408/aiq.v7i2.1701